A Reliable Load Balancing Fault Tolerant Multi-SDN Controller approach in a typical Software Defined Network - S, Sharathkumar; Sreenath, N (EAI Endorsed Transactions on Internet of Things, 2022)
INTRODUCTION: In the 21st Century, we have an emerging, modernized networking approach for efficient transfer of data in the form of packets i.e Software defined Networking (SDN). It is often recognized as the network paradigm acquired by an isolated independent control plane by the means of the underlying networking interface. As the communication medium is getting rapidly increased, the usage of the number of resources are also increasing in the same ratio, this results to connectivity problem in communication networks as well. If the development in technology is gaining more interest, the resource utilization will also increase. OBJECTIVES: In the proposed work here, we need to establish the connection between the client (or the end user) and the server by calculating the network performance using the parameters such as server response time and the throughput of the network by the method of load balancing. METHODS: This paper aims to identify the new methods or techniques to improve the performance of SDN with the increase in reliability, specifically required to improve the real-time data delivery. Alternatively, a reliable disjoint, distributed Multi- SDN controller will be used, to collect the updated network information like packet size, connectivity, packet flow etc. The methods involved are ideal controller optimization technique, distruption acquiscent technique and Maximum flow shortest route technique. RESULTS: From the results obtained by the simulation, the Reliable Load balancing Fault Tolerant Multi-SDN Controller(RLFTMS) approach is more reliable, fault tolerant compared to the other existing traditional mechanisms. CONCLUSION: Load balancing based on the server response time, throughput is being compared , this improves the server workload ditribution among various datacenters. Ultimately the customers or clients will have a great experience in terms of the reducing response time and increase in the throughput.